2005
DOI: 10.1021/jp054740b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Manganese Oxide Electrodes with Interconnected Nanowire Structure as an Anode Material for Rechargeable Lithium Ion Batteries

Abstract: Manganese oxide electrodes composed of interconnected nanowires are electrochemically synthesized in manganous acetate solution at room temperature without any template and catalyst. Annealing temperature affects the electrode morphology, crystallization, and electrochemical performance. Scanning electron microscope (SEM) results show that nanowires are uniformly distributed and sizes are about 12-18 nm in diameter; the diameter decreases to about 8-12 nm after annealing at 300 degrees C. X-ray diffraction (XR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
147
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(155 citation statements)
references
References 21 publications
6
147
2
Order By: Relevance
“…However, following calculations using a simple 1D model, it is suggested that, by [ 42 , 43 ] Mn 3 O 4 , [43][44][45] and MnO. [46][47][48] In general, rather low Coulombic effi ciencies in the fi rst cycle and rapid capacity decays with cycling were reported, the best results showing capacities of 600 mAh g − 1 after 100 cycles for a γ -MnO 2 fi lm deposited on nickel metal [ 39 ] and after 150 cycles for MnO powder. [ 48 ] Notwithstanding these disappointing results, the scarcity of systematic efforts to optimize the performance of electrodes using manganese oxides by combining materials synthesis, processing and engineering indicate that improvements could be achieved.…”
Section: Manganesementioning
confidence: 99%
“…However, following calculations using a simple 1D model, it is suggested that, by [ 42 , 43 ] Mn 3 O 4 , [43][44][45] and MnO. [46][47][48] In general, rather low Coulombic effi ciencies in the fi rst cycle and rapid capacity decays with cycling were reported, the best results showing capacities of 600 mAh g − 1 after 100 cycles for a γ -MnO 2 fi lm deposited on nickel metal [ 39 ] and after 150 cycles for MnO powder. [ 48 ] Notwithstanding these disappointing results, the scarcity of systematic efforts to optimize the performance of electrodes using manganese oxides by combining materials synthesis, processing and engineering indicate that improvements could be achieved.…”
Section: Manganesementioning
confidence: 99%
“…Carbon nanomaterials were also incorporated to enhance the electronic conductivity. [8][9][10][11][13][14][15][16][17][18][19][20][21][22][23][24] Graphene, [20] carbon nanotubes, [17,23] and carbon nanofibers [24] hae been used to fabricate manganese oxide-carbon nanocomposite anode materials. However, the high surface area of manganese oxide-carbon nanocomposites resulted in low coulombic efficiency due to the formation of a large unstable solid electrolyte interphase (SEI) during nanoparticles have demonstrated the best electrochemical performance of manganese oxide anode to date.…”
Section: Introductionmentioning
confidence: 99%
“…Submicronic materials, such as nanoparticles, nanorods, nanobelts, nanowires, nanotubes, nanofibers and urchins/orchids, mesoporous MDOs are currently investigated [9][10][11]. KMnO 4 is one of the main starting materials for synthesis of α-MnO 2 as it is not only a suitable Mn source, but it can also stabilize the crystallographic structure of MnO 2 by the presence of K + cations located in the cavities [12].…”
Section: Introductionmentioning
confidence: 99%